Trading on Commonwealth ties : a review of the structure of Commonwealth trade and the scope for developing linkages and trade in the Commonwealth - Milner, Chris (Commonwealth Secretariat LondonGB, 2008)
Identifies opportunities for stimulating trade within the Commonwealth, but warns against setting up a free trade agreement across the member states. Suggests that improving trade infrastructure - particularly roads, railways and port facilities - is a key means of lowering trading costs and boosting trade both within the Commonwealth and with non-Commonwealth countries.